Development of a multipurpose test rig - TAILTEST - Oberthor Martin (EDP Sciences, 2021)
The paper discusses an innovative multipurpose test rig designed with the aim of full-scale rotorcraft fin verification. The developed test rig includes a load application mechanism able to distribute loads representative for rotorcraft tail structure. Both conventional metallic components and innovative thermoplastic composites are used in the rotorcraft tail structure. The test rig will be designed so that a variable stiffness of the fuselage to the fin joint is achieved. Verification of the new tail structure is supported by additional experiments and numerical analyses.